Keadilan, Komitmen pada Tujuan, dan Job-relevant Information dalam Penganggaran Partisipatif - Windu Mulyasari; Slamet Sugiri (The Indonesian Journal of Accounting Research, 2013)
The relationship between participative budgeting and management performance has interested many researchers. Prior empirical studies, however, find inconsistent evidence. Shields and Shields (1998) suggest that budgetary participation does not have a direct effect on performance, but is rather conditioned on other intervening variables. The current study is aimed to investigate the interrelationship of participative budgeting with managerial performance through social, motivational, and cognitive factors. Data are collected by sending questionnaires to managers of service and manufacturing companies throughout Java. Only eighty-nine respondents fill the questionnaires. Using structural equation models, the current study finds that: (1) the direct relationship between participative budgeting and management performance is not statistically significant; (2) procedural fairness, but not distributive fairness, and job-relevant information statistically significantly affect the relationship between participative budgeting and management performance; and (3) goal commitment does not statistically significantly affect  management  performance.